Allometric Growth in Red Porgy Larvae: Developing Morphological Indices for Mesocosm Semi‐Intensive Culture. (29th November 2012) - Andrade, Carlos A. P.; Nascimento, Francisco J. A.; Nogueira, Natacha; Pimenta, Filomena; Dinis, Maria T.; Narciso, Luís
Abstract: We studied the morphological development, allometric growth, and cannibalistic behavior of Red Porgy Pagrus pagrus reared in mesocosm semi‐intensive culture. The study was conducted from hatching to 32 d after hatching (DAH). Red porgy ontogeny was characterized by strong positive allometric growth of body depth at anus (BDA) to 6.7 mm total length (TL) at about 21–22 DAH. The BDA combined with standard length (SL) in a morphometric index was found to be better correlated with dry weight than TL and provided an improved method to estimate larval growth. Mouth size also exhibited strong positive allometric growth at early larval stages that, together with inflation of the swim bladder, may have contributed to improve feeding ability, in preparation for the high energy demands of metamorphosis. A predictive regression model developed for cannibalism underestimated prey size. Cannibalism coincided with the development of acidic digestion and was first evident at 27 DAH as larvae reached about 23% of their maximum size variation. We hypothesize that cannibalism is associated with larval size and condition, but is prompted by physiological and energetic factors. The bivariate morphometric index developed in this study can be used to mitigate cannibalism by controlling larval size variation and improving feed supply. The morphological measurements and morphometric indices that result from this study provide important tools for improving red porgy larvae culture.